In situ ethylation-purge and programmed-temperature-vaporizer cold trapping-gas chromatography-mass spectrometry as an automated technique for the determination of methyl- and butyltin compounds in aqueous samples - Eiden, Ralf; Schöler, Heinz Friedrich; Gastner, Manfred (Journal of chromatography, 1998)
A new method for the determination of methyl- and butyltin compounds in aqueous samples is presented. The organotin species are derivatized in situ with sodium tetraethylborate (NaBEt4) in an 800-ml sample, purged on-line with helium and cryofocused at −40°C in the Tenax-filled glass insert of a modified split/splitless injector. The injector is equipped with a liquid nitrogen cooling and a heating wire which serves for programmed-temperature vaporization. After thermal desorption the peralkylated tin species are refocussed on the capillary GC column at 10°C followed by GC separation and mass spectrometric detection in the full scan mode. All steps are computer-controlled so that once the derivatizing reagent is added, the analysis is performed automatically. The concentration of NaBEt4, the reaction time, the purge flow-rate and the purge time were optimized. The preconcentration of sample volumes of 800 ml led to detection limits in the range of 1-2 ng Sn/l. Due to the compound specific information of the full scan mass spectra, the presented method is a powerful tool for the speciation of alkyltin compounds in aqueous samples.
Gesehen am 17.11.2022